2022
DOI: 10.3390/nano12060922
|View full text |Cite
|
Sign up to set email alerts
|

Nanoparticle-Mediated Photothermal Therapy Limitation in Clinical Applications Regarding Pain Management

Abstract: The development of new effective cancer treatment methods has attracted much attention, mainly due to the limited efficacy and considerable side effects of currently used cancer treatment methods such as radiation therapy and chemotherapy. Photothermal therapy based on the use of plasmonically resonant metallic nanoparticles has emerged as a promising technique to eradicate cancer cells selectively. In this method, plasmonic nanoparticles are first preferentially uptaken by a tumor and then selectively heated … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
15
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 36 publications
(23 citation statements)
references
References 193 publications
(233 reference statements)
0
15
0
Order By: Relevance
“…The PCE of VSe 2 /Mn-CS NSs was measured to be 34.61%, which is higher than those of the reported VS 2 nanodots (31.5%), Ti 3 C 2 NSs (30.6%), and Au nanorods (21%) (Figure f). It is reported that the PCE of some materials including Au nanostars, Ag@Ag 2 S, Ti 2 C nanoflakes, and MoSe 2 NSs might exceed 50%, while the higher temperature might lead to irreversible damage to the normal cells around the cancer cells. Especially, the overexpression of heat shock proteins triggered by hyperthermia might cause self-repair of damaged cells, leading to the tumor thermal endurance against heat stress. , On the other hand, if the PCE was too low, an ideal therapeutic effect would not be achieved. Therefore, VSe 2 /Mn-CS with an appropriate PCE makes it a potential PTA for mild PTT.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…The PCE of VSe 2 /Mn-CS NSs was measured to be 34.61%, which is higher than those of the reported VS 2 nanodots (31.5%), Ti 3 C 2 NSs (30.6%), and Au nanorods (21%) (Figure f). It is reported that the PCE of some materials including Au nanostars, Ag@Ag 2 S, Ti 2 C nanoflakes, and MoSe 2 NSs might exceed 50%, while the higher temperature might lead to irreversible damage to the normal cells around the cancer cells. Especially, the overexpression of heat shock proteins triggered by hyperthermia might cause self-repair of damaged cells, leading to the tumor thermal endurance against heat stress. , On the other hand, if the PCE was too low, an ideal therapeutic effect would not be achieved. Therefore, VSe 2 /Mn-CS with an appropriate PCE makes it a potential PTA for mild PTT.…”
Section: Resultsmentioning
confidence: 99%
“…The 3,3′,5,5′-tetramethylbenzidine (TMB) colorimetric method was used to detect the yield of •OH. H 2 O 2 with different concentrations (10,20,60,120, and 250 mM) was added into the mixture solution of TMB (6 mg mL −1 ) and 500 μg mL −1 of VSe 2 /Mn-CS. The absorbance at 652 nm were recorded by the UV− vis spectroscopy instrument.…”
Section: Methodsmentioning
confidence: 99%
“…In recent years, photothermal ablation (PTA) therapy has become a promising treatment in the management of various types of cancer with minimal invasiveness. In this approach, light energy is converted into heat energy by exploiting photothermal agents with a high-power near-infrared (NIR) laser to place cancer cells in remission (hyperthermia) ( 171 ). Cancer cells are more sensitive than normal cells to heat stress owing to the different pattern expressions of heat shock proteins that are involved in the cellular defense mechanism.…”
Section: Photothermal Ablation Therapymentioning
confidence: 99%
“…At present, clinical methods for tumor treatment mainly include surgery, chemotherapy, radiotherapy and immunotherapy, but these treatment methods have many shortcomings such as damage to normal tissues and organs, limited tumor treatment effects, and increased chances of tumor recurrence and metastasis, which seriously affect the diagnosis and treatment effects of tumors [4] [5] . Photothermal therapy (PTT), as a highly effective tumor treatment, has received wide attention in recent years due to its advantages of small invasiveness and high spatio-temporal selectivity [6][7] . Compared with traditional treatment modalities, PTT is simple, minimally invasive, safe, and has a short treatment time, and it converts the light energy of the irradiated laser into heat energy in the form of non-thermal radiation through a photothermal agent, thus achieving effective killing of tumor cells [8] .…”
Section: Introductionmentioning
confidence: 99%